Three essays on mutual funds - Qiao, Zheng (2014)
In essay one, for an actively managed equity mutual fund, style dispersion describes how widely fund stockholdings are dispersed along size, value, and momentum dimensions. A simple benefit-cost analysis suggests that style dispersion can reflect a fund manager's investment ability and predict fund performance. Our empirical analysis confirms this. We have two major findings. First, style dispersion, especially that along size dimension, is significantly positively related with fund performance. Second, a high-size-dispersion fund manager exhibits significantly better stock selection skill than a low-size-dispersion fund manager does, especially when investing in stocks with different size characteristics from the average fund size style. We also conduct various robustness tests to show that size dispersion is distinct from all existing predictors of fund performance.